2005
DOI: 10.1002/hlca.200590211
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Resorcinarenes Under Alkaline Conditions

Abstract: The preparation of functionalized resorcinarenes is described. Thus, 2-nitroresorcinol (= 2-nitrobenzene-1,2-diol), 2-acetylresorcinol (= 1-(2,6-dihydroxyphenyl)ethanone), and 2,6-dihydroxybenzoic acid were treated with formaldehyde in alkaline medium to give the corresponding resorcinarenes 1 -3 (Scheme 1). This method is also applicable for resorcinol (= benzene-1,3-diol) itself, but the yields are poorer. In this case, the molecule formed is the simplest resorcinarene 4 on which a number of substituents ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…3 There are a large number of known derivatives that are obtained by functionalisation at position 2 and of the hydroxy groups. The cyclic structure of the molecule and the symmetrical arrangement of two hydroxy groups provide the molecule with unique possibilities for the formation of a series of chiral cyclic derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…3 There are a large number of known derivatives that are obtained by functionalisation at position 2 and of the hydroxy groups. The cyclic structure of the molecule and the symmetrical arrangement of two hydroxy groups provide the molecule with unique possibilities for the formation of a series of chiral cyclic derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we attempted a base-catalyzed approach. Bourgeois has effected the macrocyclization of 2-nitroresorcin [4]arene using sodium hydroxide in water; [34] instead we used a solution of sodium methoxide in methanol so as not to hydrolyze the methyl ester. Upon quenching with acid and filtration, a complex mixture was observed that showed 1 H NMR signals at approximately 6.3 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…The condensation reaction between formaldehyde and 2-nitroresorcinol and its analogs seems to take place in the irreversible reaction, so it is unknown whether to form a tetramer, pentamer, or hexamer [36].…”
Section: Condensation Of Resorcinol With Formaldehyde Under Acidic Comentioning
confidence: 99%